Risk factors associated with health literacy among community residents in China based on multiple correspondence analysis and ordinal logistic regression - Mengqian Gao; Shuo Yang; Hongtao Zhang; Ying Huang; Hui Xiao; Zhanming He; Chao Qiu; Jianyun Lu (Scientific Reports)
Abstract Health literacy is crucial in individuals’ ability to make informed health decisions and manage chronic conditions. This study aimed to assess the levels of health literacy and identify socio-demographic factors associated with health literacy among residents aged 15−69 years in Baiyun District, Guangzhou. A cross-sectional survey was conducted among 2630 participants using the China Health Literacy Survey (CHLS) questionnaire between 2019 and 2024. Ordinal logistic regression (OLR) was performed to identify factors associated with health literacy. Multiple Correspondence Analysis (MCA) was used to explore the interrelationships between categorical variables such as age, education, and health literacy. The mean health literacy score was 47.31 (SD = 11.41), with 34.5% of participants having adequate health literacy. The OLR results showed that lower education levels were significantly associated with a reduced likelihood of having adequate health literacy. Participants with less than junior high school education ( $$\hat{β}$$ = −1.71, 95% CI: −2.06, −1.37, P < 0.001) and those with junior or senior high school education ( $$\hat{β}$$ = −1.24, 95% CI: −1.40, −1.07, P < 0.001) were less likely to have adequate health literacy compared to those with college or higher education. Age was also significantly associated with health literacy, with younger participants (aged 15–44 years) having a higher likelihood of adequate health literacy ( $$\hat{β}$$ = 0.82, 95% CI: 0.58, 1.06, P < 0.001). MCA further revealed that younger, higher-educated individuals clustered in the upper-left quadrant, reflecting higher health literacy, while older, less-educated individuals were positioned in the lower-right quadrant, indicating lower health literacy. Education and age were significant determinants of health literacy in Baiyun District, Guangzhou. These findings emphasize the need for targeted health literacy interventions, particularly for older and less-educated populations. Public health policies should focus on improving educational opportunities and providing tailored health education programs to enhance health literacy, thereby reducing health disparities.